Pengaruh Discrete Trial Training terhadap Perilaku Ekolalia pada Siswa Kelas 1 - Dian Yuniar Wardani S; Angger Timansah; Bhennita Sukmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The primary objective of this study was to determine the effect of the discrete trail training technique on echolalia behavior in first-grade students. This study used the Single Subject Research (SRR) method, a research approach that focuses on observing a single subject to evaluate changes or the impact of an intervention. The results are expected to provide insight into the potential of the discrete trail training technique in supporting the abilities of students with echolalia. The expected output is data that can demonstrate the effectiveness of the discrete trail training technique in the therapy process and provide a foundation for the discrete trail training technique. Keywords: Discrete Trail Training, Echolalia Behavior, First-Grade Students at Yima Elementary School, Bondowoso